Enhanced mechanical properties of chitosan/EDTA-GO nanocomposites thin films - Ahmad Blya, Nur Ily Syuhada; Huang, Nay Ming; Kumar, S. Vijay; Lim, Hong Ngee; Abdul Rahman, Saadah; Thien, Gregory S. H.; Ibrahim, Nor Azowa; Ahmad @ Ayob, Mansor; Moradihamedani, Pourya (Penerbit Universiti Kebangsaan Malaysia, 2014)
Nanocomposite thin films of chitosan/graphene oxide (CS/GO) and chitosan/ EDTA-GO (CS/EDTA-GO) were prepared by environmental friendly method and the properties were compared. The experimental results showed fine dispersion of GO and EDTA-GO in CS matrix and some interaction occur between the filler and the CS matrix that leads to better distribution of stress transfer. At 0.5 wt. %, both CS/GO and CS/EDTA-GO experienced maximum tensile stress by 51 and 71% compared with CS. Moreover, the elongation at break for both nanocomposites increases and the amount of filler increases.